2020
DOI: 10.1093/trstmh/traa077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of human papillomavirus infection in Huzhou City, eastern China, 2018–2019

Abstract: Background Human papillomavirus (HPV) infection is involved in cervical cancer development, and hence understanding its prevalence and genotype distribution is important. However, there are few reports on the prevalence and genotype distribution of HPV in the city of Huzhou in China. Methods In this retrospective cross-sectional study, 11,506 women who visited Huzhou Maternity & Child Health Care Hospital between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
8
13
1
Order By: Relevance
“…That China is vast in territory and huge in population, coupled with unbalanced development, and insufficient awareness of prevention and screening in earlier years and nonstandard cervical cancer screening in certain underdeveloped areas resulted in the regional differences in the epidemiology of HPV and cervical cancer. The overall infection rate of hrHPV in different regions of China was 8.8%-25.7% in recent years [4][5][6][19][20][21][22][23][24][25]. Our study showed that the overall infection rate of hrHPV was 20.3%, which was similar to most reviews or researches on the nationwide prevalence of hrHPV infection in China [4][5][6].…”
Section: Discussionsupporting
confidence: 83%
“…That China is vast in territory and huge in population, coupled with unbalanced development, and insufficient awareness of prevention and screening in earlier years and nonstandard cervical cancer screening in certain underdeveloped areas resulted in the regional differences in the epidemiology of HPV and cervical cancer. The overall infection rate of hrHPV in different regions of China was 8.8%-25.7% in recent years [4][5][6][19][20][21][22][23][24][25]. Our study showed that the overall infection rate of hrHPV was 20.3%, which was similar to most reviews or researches on the nationwide prevalence of hrHPV infection in China [4][5][6].…”
Section: Discussionsupporting
confidence: 83%
“…In this present survey, the overall infection rate of high‐risk HPV was 14.26% in Chongqing in China, which was higher than that in Huzhou (13.3%), 9 and lower than in Beijing (21.06%), 14 Guangdong Province (15.66%) 15 …”
Section: Discussionmentioning
confidence: 44%
“…The prevalence rate of HPV infection changes in different countries, 6–8 but also varies in different regions of China 9,10 . It is essential for the prevention and treatment of local cervical cancer to investigate the distribution of HPV genotypes in regions areas (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HPV infection rates differ across regions in China [ 6 8 ] Here, we analyzed the HPV prevalence trends from 2016 to May 2021 and found that the overall infection rate was 18.10% (Table 1 ). This is higher than reported in Yunnan (12.9%) [ 6 ], Shanghai (17.92%) [ 8 ], Xinjiang (14.02%) [ 9 ], and Huzhou (15.5%) [ 10 ], and lower than reported in Guangzhou (26.0%) [ 7 ], Sichuan (23.84%) [ 11 ], and Chongqing (19.9%) [ 12 ]. In addition to cultural background and living habits, ethnicity may be an important contributing factor to HPV prevalence in different regions.…”
Section: Discussionmentioning
confidence: 57%